Handbook of frozen foods (Marcel Dekker, 2004)
Collecting an impressive amount of professional expertise on frozen food science, technology, and engineering, this reference describes the manufacture, processing, inspection, and safety of frozen foods—surveying a wide range of topics in frozen food packaging, quality, and shelf-life from more than 50 of the most respected leaders in the field.